SELF-REPORTED HEARING PROBLEMS AMONG OLDER ADULTS (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Annotatsion: Population-based epidemiological data examining the relationship between self-reported hearing complaints and objectively measured hearing thresholds in older adults are limited. Effective planning of hearing health care, including the development and implementation of adult screening programs, depends on population-based epidemiological evidence describing the prevalence of self-reported hearing complaints and their association with objectively measured hearing impairment. Hearing impairment is highly prevalent among older adults. The purpose of this study was to assess the prevalence of self-reported hearing-related problems—namely hearing difficulties, difficulty understanding speech in noisy environments, tinnitus, and hyperacusis—and to examine their relationship with measured hearing thresholds in an older population using a cross-sectional, randomly selected, unscreened sample.